Is History Losing its Popularity as an Academic Discipline? A Case Study of USA and Nigeria - Billy Agwanda (Journal of Universal History Studies)
During the past few decades, there has been attacks directed towards the discipline of history especially from postmodernist scholars who continue to emphasize that history is simply a form of narrative with questionable objectivity. These writers construe history as human construct that signifies and facilitates our understanding of the past. Throughout the development in human societies, History was a fundamental pillar and was once conceived as a noble discipline reserved only for the Royal families and the Nobles surrounding them. However, the 21st century is recording one of the lowest points for the discipline which has increasingly come under threat from the transformations in the dynamics of the society fuelled by a deeply entrenched capitalist system that influences the choice of careers in modern day society. Consequently, History has been relegated to a selective subject as a complement to other disciplines that are perceived to have higher income capacities such as international studies and diplomacy. This paper therefore, attempts to examine the study of History as an academic discipline in the United States and Nigeria by identifying the causes for such diminishing popularity of History as an academic discipline.